Boosting Critical Thinking with STEM-Based Nanolearning in Reaction Rate Studies - Baihaqie, Arya Girald; Kurniasih, Dedeh; Kurniawan, Rizmahardian A.; Nufus, Zahratun (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the effect of STEM-based Nanolearning implementation in improving students’ critical thinking skills at SMAIT Al-Fityan Kubu Raya. This study used a one-group pre-test-post-test quasi-experimental research design. The population in this study consisted of 59 people. The sample selection for this study was carried out using purposive sampling, specifically targeting 19 students from class XI Ikhwan at SMA IT Al-Fityan Kubu Raya. The data collection technique used was a critical thinking skills test, which includes four indicators: interpretation, evaluation, analysis, and explanation. The results of the pretest research obtained at 35.53 were categorized as low and the posttest obtained at 82.89. Data analysis was conducted using normality test pretest sig 0.062 and posttest 0.070 normally distributed, hypothesis test obtained sig 0.00 <0.05, H1 accepted, and effectiveness test resulted in N-gain value of 0.75. This shows that Nanolearning has a significant effect on critical thinking skills of class XI Ikhwan SMA IT Al - Fityan Kubu Raya.